Healthy and stable lighting via single-component white perovskite nanoplates. Issue 32 (2nd August 2022) - Cui, Hao; Su, Zhan; Ji, Yu; Lan, Tao; Zhang, Jian-Bin; Ma, Juan; Yang, Liu; Chen, Yu-Hui; Shen, Hao-Ran; Wang, Jiaqian; Liu, Lihui; Cao, Kun; et al.
Abstract : Single-component CsMn x Pb1− x Br3 NPLs emitted healthy white light without harmful deep blue light (400–450 nm). Their white LED worked continuously for 240 minutes with a lower color drift of (±0.006, ±0.004). Abstract : Single-component healthy white light was achieved via Mn 2+ post-doping into blue perovskite nanoplates (NPLs). The white light consists of two complementary colors, sky-blue (482 nm) and orange-red (610 nm), without harmful deep blue light (400–450 nm), which realizes the Commission Internationale de I′Eclairage (CIE) coordinates of (0.33, 0.33) (standard pure white light) and a color temperature of 6000 K. Benefitting from the lattice shrinking via Mn 2+ doping, the stability of white NPLs toward long-term storage, UV light, heat, and polar solvents was greatly improved. Finally, a healthy and stable white light-emitting diode (WLED) was fabricated via down-conversion of a UV light LED with our white perovskite NPLs, and the WLED worked continuously for 240 minutes with a color drift of only (±0.006, ±0.004) and with a half lifetime ( T 50 ) of 212 minutes.